Neuromodulation for mood and memory: from the engineering bench to the patient bedside. (February 2015) - Deng, Zhi-De; McClintock, Shawn M; Oey, Nicodemus E; Luber, Bruce; Lisanby, Sarah H
Highlights: Newly approved antidepressants include TMS and deep TMS. Spatially and temporally precise tools can induce lasting changes in neuroplasticity. ECT effects on mood and memory can be decoupled. Computer simulation of induced fields provides a rational basis for device design. Abstract : Brain stimulation, in the form of electroconvulsive therapy (ECT), has long been a gold standard treatment for depression, but today, the field of neuromodulation is rapidly changing with the advent of newer and more precise tools to alter neuroplasticity and to treat brain-based disorders. Now there are new means to induce focal seizures, as with magnetic seizure therapy (MST), or modifications to ECT. There are also surgical approaches to target brain circuits via implanted stimulators placed in the brain or on cranial nerves. Finally, there are noninvasive subconvulsive approaches for the transcranial application of either electric or magnetic fields. Collectively, these tools have transformed the face of neurotherapeutics and informed our understanding of the brain basis of complex neurobehavioral conditions.